E-travel Adoption by Small Travel Enterprises (STEs): An Initial Study in Indonesia and Malaysia - Pujani, Vera; Yahya, Yazrina; Alfitman, Alfitman; Nazir, Refdinal (UI Scholars Hub, 2021)
This paper aims to investigate e-travel adoption of tourism industries in Indonesia and Malaysia particularly by STEs. The qualitative research was undertaken using case analysis from in-depth interviews of 10-STEs as intial study both in Indonesia and Malaysia. The finding result of e-travel adoption by STEs in a cross-cultural study was identified from the findings present in the initial study based on personal, organizational and website characteristics. The majority of personal characteristics were relatively similar in both countries. However, few differences are present in organizational and website characteristics. E-travel adoption in both countries is influenced by the business experiences of owners/managers, various technological aspects, and the nature of use and benefits. The following study, the user-based survey would be undertaken to complete The e-travel adoption model in Indonesia and Malaysia.